2022
DOI: 10.1021/acsnano.2c06749
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastable Super-Hydrophobic Surface with an Ordered Scaly Structure for Decompression and Guiding Liquid Manipulation

Abstract: Directional droplet manipulation is very crucial in microfluidics, intelligent liquid management, etc. However, excessive liquid pressure tends to destroy the solid–gas–liquid (SAL) composite interface, creating a highly adhesive surface, which is not conducive to liquid transport. Herein, we propose a strategy to enhance the surface durability, in which the surface cannot withstand liquid pressure only by “blocking” but must instead guide liquid transport for “decompression”. Learning from the water resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 58 publications
(85 reference statements)
0
13
0
Order By: Relevance
“…We use TiN films as they result in intermediate heights compared to the other tested materials (Figure b). First, we investigate the wing structure of Papilio paris (top Figure a), which shows interesting coloring effects induced by its nanostructure. ,, This was followed by replicating the pattern of shark skin (triangular shape with parallel stripes), as it is one of the best candidate designs for reducing hydrodynamic drag (middle Figure a). ,,, Finally, we looked into meeting the technological need for novel adhesion pads, which has lead the scientific community to study the pad epithelia of frogs (bottom Figure a). , Their nanostructure provides elevated adhesion to almost all surfaces and, thus, it is ideal for various applications such as adhesion under wet conditions and enhanced friction control. , SEM images show the patterned area (Figure b) and high-resolution confocal microscopy is utilized to investigate the patterns’ surface morphology and roughness (Figure c). To understand the height variation, we perform a more detailed analysis where we plot the height vs distance (dash lines in Figure c) over the patterned area (Figure d).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We use TiN films as they result in intermediate heights compared to the other tested materials (Figure b). First, we investigate the wing structure of Papilio paris (top Figure a), which shows interesting coloring effects induced by its nanostructure. ,, This was followed by replicating the pattern of shark skin (triangular shape with parallel stripes), as it is one of the best candidate designs for reducing hydrodynamic drag (middle Figure a). ,,, Finally, we looked into meeting the technological need for novel adhesion pads, which has lead the scientific community to study the pad epithelia of frogs (bottom Figure a). , Their nanostructure provides elevated adhesion to almost all surfaces and, thus, it is ideal for various applications such as adhesion under wet conditions and enhanced friction control. , SEM images show the patterned area (Figure b) and high-resolution confocal microscopy is utilized to investigate the patterns’ surface morphology and roughness (Figure c). To understand the height variation, we perform a more detailed analysis where we plot the height vs distance (dash lines in Figure c) over the patterned area (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…Copyright 2009 American Chemical Society. Middle panels reprinted with permission from refs and . Copyright 2022 and 2018 American Chemical Society.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the view of mechanism, the surface energy release of fluid contributes to the specific transporting process that is determined by the wettability contrast. While the liquid was confined by the hydrophilic track, a series of manipulating trials can be achieved such as unidirectional transport, selective release, spontaneous mixing, etc. …”
Section: Introductionmentioning
confidence: 99%
“…At present, superwetting materials have been extensively used in self-cleaning, 3 anti-fogging, 4 anti-icing, 5,6 corrosion protection, [7][8][9] oil-water separation, [10][11][12] and other fields. With further research on superwetting materials, it is found that the superwetting interface has a special three-phase contact area and controllable microfluidic characteristics, which can manipulate the transport of liquid, [13][14][15] gas, 16,17 and ions. [18][19][20] Researchers have applied the special mass transfer performance to various chemical reactions to control the adsorption of reactants and desorption of products, so as to improve reaction efficiency, such as electrochemical reactions, [21][22][23][24] photocatalytic reactions, 25,26 bioelectronic reactions, 27 and organic synthesis reactions.…”
Section: Introductionmentioning
confidence: 99%